Autocrine insulin-like growth factor 2 signaling as a potential target in the associated development of pulmonary emphysema and cancer in smokers - Hye-Jin Boo; Hye-Young Min; Heung-Bin Lim; Euni Lee; Ho-Young Lee (BMC, 2024)
Abstract Background Tobacco smoking causes pulmonary inflammation, resulting in emphysema, an independent risk factor for lung cancer. Induction of insulin-like growth factor 2 (IGF2) in response to lung injury by tobacco carcinogens, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol and polycyclic aromatic hydrocarbon benzo[a]pyrene in combination (NB), is critical for the proliferation of alveolar type 2 cells (AT2s) for lung repair. However, persistent IGF2 overexpression during NB-induced severe injury results in hyperproliferation of AT2s without coordinated AT2-to-AT1 differentiation, disrupting alveolar repair, which leads to the concurrent development of emphysema and lung cancer. The current study aims to verify the role of IGF2 signaling in the associated development of emphysema and cancer and develop effective pharmaceuticals for the diseases using animal models that recapitulate the characteristics of these chronic diseases. Methods The pathogenesis of pulmonary emphysema and cancer was analyzed by lung function testing, histological evaluation, in situ zymography, dihydroethidium staining, and immunofluorescence and immunohistochemistry analyses utilizing mouse models of emphysema and cancer established by moderate exposure to NB for up to seven months. Results Moderate NB exposure induced IGF2 expression in AT2s during the development of pulmonary emphysema and lung cancer in mice. Using AT2-specific insulin receptor knockout mice, we verified the causative role of sustained IGF2 signaling activation in AT2s in emphysema development. IGF2-targeting strategies, including voltage-dependent calcium channel blocker (CCB) and a neutralizing antibody, significantly suppressed the NB-induced development of emphysema and lung cancer. A publicly available database revealed an inverse correlation between the use of calcium channel blockers and a COPD diagnosis. Conclusions Our work confirms sustained IGF2 signaling activation in AT2s couples impaired lung repair to the concurrent development of emphysema and cancer in mice. Additionally, CCB and IGF2-specific neutralizing antibodies are effective pharmaceuticals for the two diseases.